2016
DOI: 10.1021/acs.jafc.6b04101
|View full text |Cite
|
Sign up to set email alerts
|

Antroquinonol, a Ubiquinone Derivative from the Mushroom Antrodia camphorata, Inhibits Colon Cancer Stem Cell-like Properties: Insights into the Molecular Mechanism and Inhibitory Targets

Abstract: Antroquinonol (ANQ) is a ubiquinone derivative from the unique mushroom Antrodia camphorata, which exhibits broad-spectrum bioactivities. The effects of ANQ on cancer stem cell-like properties in colon cancer, however, remain unclear. In this study, we found that ANQ inhibited growth of colon cancer cells. The 50% growth inhibitions (GI) of ANQ on HCT15 and LoVo were 34.8 ± 0.07 and 17.9 ± 0.07 μM. Moreover, ANQ exhibited inhibitory activities toward migration/invasion and tumorsphere formation of colon cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…These results suggest that the cell survival benefits from autophagy, with implications for the long-term resolution of colorectal cancer (Kantara et al, 2014). Antroquinonol, isolation from mushroom Antrodia camphorata, triggered PI3K/Akt/β-catenin signaling and could be a favorable cancer prevention agent for colon CSCs (Lin et al, 2017). Bitter melon extracts, isolated from Momordica charantia, inhibit CCSCs by affecting energy homeostasis in addition to increase Beclin-1, Atg7 and 12 autophagic protein in HT-29, and SW480 colon cancer cells (Kwatra et al, 2013).…”
Section: Autophagy In Colon Cancer Stem Cellsmentioning
confidence: 92%
“…These results suggest that the cell survival benefits from autophagy, with implications for the long-term resolution of colorectal cancer (Kantara et al, 2014). Antroquinonol, isolation from mushroom Antrodia camphorata, triggered PI3K/Akt/β-catenin signaling and could be a favorable cancer prevention agent for colon CSCs (Lin et al, 2017). Bitter melon extracts, isolated from Momordica charantia, inhibit CCSCs by affecting energy homeostasis in addition to increase Beclin-1, Atg7 and 12 autophagic protein in HT-29, and SW480 colon cancer cells (Kwatra et al, 2013).…”
Section: Autophagy In Colon Cancer Stem Cellsmentioning
confidence: 92%
“…Recent studies have reported that Antroquinonol induces apoptosis and autophagy of pancreatic cancer cells [ 156 ]. In colon cancer, ANQ has been found to suppress stem cell-like properties by targeting PI3K/AKT/β-catenin signalling [ 157 ].…”
Section: Natural Compoundsmentioning
confidence: 99%
“…[17][18][19][20] Antroquinonol, a ubiquinone derivate that has been isolated from the solid-state fermentation mycelium of A. camphorata, 21 has been shown to have bioactive properties, such as anticancer and anti-inflammatory activity. [22][23][24][25][26][27][28] It is also reported that antroquinonol could lower brain amyloid-levels and improve spatial learning and memory in a transgenic mouse model of Alzheimer's disease. 29 Generally, antroquinonol cannot be biosynthesized in submerged fermentation.…”
Section: Introductionmentioning
confidence: 98%
“…Several bioactive compounds were isolated and identified from A. camphorata , such as terpenoids and polysaccharides . Antroquinonol, a ubiquinone derivate that has been isolated from the solid‐state fermentation mycelium of A. camphorata , has been shown to have bioactive properties, such as anticancer and anti‐inflammatory activity . It is also reported that antroquinonol could lower brain amyloid‐β levels and improve spatial learning and memory in a transgenic mouse model of Alzheimer's disease .…”
Section: Introductionmentioning
confidence: 99%